Positive electrode active material and preparation method thereof, positive plate and battery

By using hollow spherical lithium manganese iron phosphate in ternary material batteries and adjusting its proportion and particle size, the problem of difficulty in taking into account cost, rate performance and cycle performance in the prior art is solved, and efficient and economical battery performance improvement is achieved.

CN119852349APending Publication Date: 2025-04-18EVE POWER CO LTD

Patent Information

Application Number
CN202411817186.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

The prior art is difficult to take into account both the rate performance and cycle performance of ternary material batteries while reducing costs.

Method used

Using a positive electrode active material including ternary materials and hollow spherical lithium manganese phosphate, a battery with excellent rate performance and circulation performance is formed by adjusting the ratio and particle size of lithium manganese phosphate.

Benefits of technology

It achieves the improvement of the rate performance, cycle performance and energy density of the battery while reducing costs, and improves the electrochemical performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119852349A_ABST
    Figure CN119852349A_ABST
Patent Text Reader

Abstract

The invention provides a positive active material and a preparation method thereof, a positive plate and a battery, and belongs to the technical field of batteries, the positive active material comprises a ternary material and lithium manganese iron phosphate; wherein the mass of the lithium manganese iron phosphate is A, the total mass of the ternary material and the lithium manganese iron phosphate is B, and A / B is more than 0 and less than 50%; the lithium manganese iron phosphate is of a hollow spherical structure, and the median particle size of the lithium manganese iron phosphate is 0.5-3 microns. According to the positive electrode active material provided by the embodiment of the invention, the cost of the positive electrode active material can be reduced, relatively high rate capability, cycle performance and energy density are considered, and the comprehensive electrochemical performance is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and in particular to a positive electrode active material and a preparation method thereof, a positive electrode slurry, a positive electrode sheet and a battery. Background Art

[0002] Due to the scarcity of cobalt and nickel, the upstream metal raw materials of the new energy industry chain (cobalt and nickel account for 0.43% and 0.01% of the country's non-ferrous metal minerals, respectively), the cost of ternary materials is relatively high. Compared with the precious metal materials cobalt and nickel in ternary materials, the main metal elements in lithium manganese iron phosphate are manganese and iron, and the market price is relatively low, which can ensure a lower cost. In addition, from a structural perspective, compared with the ternary materials with layered structures, lithium manganese iron phosphate with an olivine structure can be more stable during the charging and discharging process, and even if all lithium ions are removed during the charging process, there will be no problem of structural collapse. At the same time, the phosphorus (P) atoms in lithium manganese iron phosphate form PO4 tetrahedrons through strong PO covalent bonds, and it is difficult for O atoms to escape from the structure, which also makes lithium manganese iron phosphate have high safety and stability. At present, the cycle of ternary materials on the market is mostly between 1000 and 2000 weeks, and the cycle period is relatively short. However, lithium manganese iron phosphate has a relatively stable olivine structure, and the cycle period can reach more than 2000 weeks, and lithium manganese iron phosphate has better cycle performance. In addition, the particle size of conventional ternary materials is generally between 6 and 10 microns. Due to the large particles, the lithium ion diffusion path is long, and the high-rate performance is relatively poor. However, ternary materials have a higher gram capacity, that is, a higher energy density.

[0003] Based on the advantages and disadvantages of ternary materials and lithium iron manganese phosphate, ternary materials and lithium iron manganese phosphate are usually mixed for use to solve the problem of high cost. However, in related technologies, single crystal ternary materials and single crystal lithium iron manganese phosphate are usually mixed, which can reduce costs but is difficult to take into account electrochemical properties such as rate performance and cycle performance. Summary of the invention

[0004] The embodiments of the present application provide a positive electrode active material and a preparation method thereof, a positive electrode sheet and a battery, which can reduce costs while taking into account rate performance and cycle performance, thereby improving electrochemical performance.

[0005] In a first aspect, an embodiment of the present application provides a positive electrode active material, including a ternary material and lithium manganese iron phosphate;

[0006] Wherein, the mass of lithium manganese iron phosphate is A, and the total mass of the ternary material and lithium manganese iron phosphate is B, satisfying: 0<A / B<50%;

[0007] Lithium manganese iron phosphate has a hollow spherical structure, and the median particle size of lithium manganese iron phosphate is 0.5μm-3μm.

[0008] In some embodiments, the specific surface area of ​​lithium manganese iron phosphate is 11m 2 / g-21m 2 / g;

[0009] And / or, the tap density of lithium manganese iron phosphate is 0.3g / cm 3 -0.8g / cm 3 .

[0010] In some embodiments, the molecular formula of the ternary material is LiNi a Co b Mn c M d O2; where a+b+c+d=1, a≥0.5, b≤0.3, 0≤d≤0.05;

[0011] M is selected from at least one of Zr, Sr, W, B, Nb, Al, Mg and Ti.

[0012] In some embodiments, the median particle size of the ternary material is 3 μm to 10 μm.

[0013] In some embodiments, the lithium manganese iron phosphate includes a lithium manganese iron phosphate body and a carbon coating layer coating the lithium manganese iron phosphate body.

[0014] In a second aspect, an embodiment of the present application provides a method for preparing a positive electrode active material, which is used to prepare the positive electrode active material as described above, comprising:

[0015] Provide ternary materials and lithium manganese iron phosphate;

[0016] The ternary material and lithium manganese iron phosphate are mixed in proportion to obtain a positive electrode active material.

[0017] In some embodiments, before providing the ternary material and lithium manganese iron phosphate, the method further includes:

[0018] Preparation of lithium manganese iron phosphate;

[0019] The preparation of lithium manganese iron phosphate includes:

[0020] Adding a phosphoric acid solution into a lithium source solution to react, thereby obtaining a hollow spherical lithium phosphate precursor;

[0021] Dispersing ferrous salt, manganese salt and lithium phosphate precursor in a solvent, and reacting to form lithium manganese iron phosphate precursor;

[0022] The lithium iron manganese phosphate precursor is sintered for the first time to obtain lithium iron manganese phosphate.

[0023] In some embodiments, a phosphoric acid solution is added to a lithium source solution to react to obtain a hollow spherical lithium phosphate precursor, including:

[0024] Add the phosphoric acid solution to the lithium hydroxide solution, stir at room temperature for 2-4 hours, and filter to obtain a first filtrate;

[0025] After the first filtered product is dried, a hollow spherical lithium phosphate precursor is obtained.

[0026] In some embodiments, the molar ratio of the ferrous salt to the manganese salt is 1:9-9:1;

[0027] And / or, the ratio of the sum of the amounts of the ferrous salt and the manganese salt to the amount of the lithium phosphate precursor is 1:1.

[0028] In some embodiments, the lithium manganese iron phosphate precursor is subjected to a first sintering, comprising:

[0029] In a protective atmosphere, the lithium manganese iron phosphate precursor is sintered at a temperature of 150°C-200°C for 5h-8h.

[0030] In some embodiments, after sintering the lithium manganese iron phosphate precursor, the method further comprises:

[0031] The sintered lithium manganese iron phosphate precursor is mixed with a carbon source and a first additive to obtain a coating material;

[0032] The coating material is sintered for a second time to obtain lithium manganese iron phosphate with a carbon coating layer.

[0033] In some embodiments, the mass proportion of the carbon source in the coating material is 10%-20%;

[0034] And / or, in the coating material, the first additive comprises at least one of Mg, Ti, Nb, Nd, Zr and Al, and the addition ratio of the first additive is 0 ppm-6000 ppm.

[0035] In some embodiments, the coating material is subjected to a second sintering, comprising:

[0036] The coating material is sintered at a temperature of 550°C-750°C for 5h-8h.

[0037] In some embodiments, before providing the ternary material and lithium manganese iron phosphate, the method further includes:

[0038] Preparation of ternary materials;

[0039] The preparation of ternary materials includes:

[0040] Mixing a ternary material precursor, lithium carbonate and a second additive to obtain a first mixed material;

[0041] Under an oxygen-containing atmosphere, performing a third sintering on the first mixed material to obtain a first sintered material;

[0042] The first sintered material is crushed to obtain a ternary material.

[0043] In some embodiments, the second additive contains at least one of Zr, Sr, W, B, Nb, Al, Mg, and Ti.

[0044] In some embodiments, performing a third sintering on the first mixed material in an oxygen-containing atmosphere comprises:

[0045] In an atmosphere with an oxygen concentration of ≥95%, placing the first mixed material in a sintering furnace for sintering;

[0046] During the sintering process, the sintering furnace is first heated from room temperature to 450°C-600°C at a heating rate of 5°C / min, and kept warm for 3h-5h. Then, the sintering furnace is heated to 700°C-900°C at a heating rate of 5°C / min, and kept warm for 6h-10h.

[0047] In a third aspect, an embodiment of the present application provides a positive electrode sheet, comprising a positive electrode foil and a positive electrode active layer coated on the positive electrode foil;

[0048] Wherein, the positive electrode active layer comprises the positive electrode active material as described above;

[0049] And / or, the positive electrode active material prepared by the method for preparing the positive electrode active material as described above.

[0050] In a fourth aspect, an embodiment of the present application provides a battery, comprising the positive electrode sheet as above.

[0051] Beneficial effects of the embodiments of the present application:

[0052] In an embodiment of the present application, the positive electrode active material includes a ternary material and lithium iron manganese phosphate. Among them, the mass of lithium iron manganese phosphate is A, and the total mass of the ternary material and lithium iron manganese phosphate is B, which satisfies: 0<A / B<50%. Lithium iron manganese phosphate has a hollow spherical structure, and the median particle size of lithium iron manganese phosphate is 0.5μm-3μm. By adding lithium iron manganese phosphate to the positive electrode active material, the amount of ternary material can be reduced, thereby reducing the cost of the positive electrode active material. Lithium iron manganese phosphate has a hollow spherical structure, and the median particle size is in the range of 0.5μm-3μm, and has excellent rate performance. Making the mass A of lithium iron manganese phosphate and the total mass B of the ternary material and lithium iron manganese phosphate satisfy 0<A / B<50%, the cost of the positive electrode active material can be reduced while taking into account higher rate performance, cycle performance and energy density, thereby improving the comprehensive electrochemical performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0053] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For those skilled in the art, other drawings can be obtained based on these drawings without creative work.

[0054] Figure 1 Schematic diagram of the synthesis process of hollow spherical lithium manganese iron phosphate in the embodiment of the present application;

[0055] Figure 2 This is a test result analysis chart of the 3C capacity retention rate in Comparative Example 1;

[0056] Figure 3 This is a test result analysis chart of the 3C capacity retention rate in Comparative Example 2;

[0057] Figure 4 3C capacity retention rate test result analysis chart in Example 1 of the present application;

[0058] Figure 5 This is an analysis chart of the cycle performance test results of Example 1 of the present application. DETAILED DESCRIPTION

[0059] The technical solutions in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without making creative work are within the scope of protection of the present application. In addition, it should be understood that the specific implementation methods described herein are only used to illustrate and explain the present application, and are not used to limit the present application.

[0060] In the first aspect, the embodiment of the present application provides a positive electrode active material including a ternary material and lithium iron manganese phosphate. Among them, the mass of lithium iron manganese phosphate is A, and the total mass of the ternary material and lithium iron manganese phosphate is B, satisfying: 0<A / B<50%. Lithium iron manganese phosphate has a hollow spherical structure, and the median particle size of lithium iron manganese phosphate is 0.5μm-3μm. By adding lithium iron manganese phosphate to the positive electrode active material, the amount of ternary material can be reduced, thereby reducing the cost of the positive electrode active material. Lithium iron manganese phosphate has a hollow spherical structure, and the median particle size is in the range of 0.5μm-3μm, and has excellent rate performance. Making the mass A of lithium iron manganese phosphate and the total mass B of the ternary material and lithium iron manganese phosphate satisfy 0<A / B<50%, the cost of the positive electrode active material can be reduced while taking into account higher rate performance, cycle performance and energy density, thereby improving the comprehensive electrochemical performance.

[0061] Among them, hollow spherical lithium manganese iron phosphate can provide a wider and smoother diffusion channel, and compared with solid structure lithium manganese iron phosphate, hollow spherical lithium manganese iron phosphate can reduce the diffusion distance of lithium ions inside the material, thereby increasing the diffusion rate of lithium ions. When hollow spherical lithium manganese iron phosphate is used in batteries, it can withstand volume changes during battery charging and discharging, which helps to maintain the cycle stability of the material. Due to the increased lithium ion diffusion rate, hollow spherical lithium manganese iron phosphate can respond to current changes more quickly during charging and discharging, thereby showing better rate performance.

[0062] The lithium manganese iron phosphate provided in the embodiment of the present application has a hollow spherical structure and a small particle size, with a median particle size of 0.5 μm-3 μm, which further shortens the diffusion distance of lithium ions inside the material. When applied to a battery, the battery can respond to changes in current more quickly, thereby improving the rate performance of the battery. The smaller particle size also helps to reduce the agglomeration problem of the positive electrode active material and improve the dispersibility and stability.

[0063] The embodiment of the present application forms a positive electrode active material by compounding lithium manganese iron phosphate that meets the above conditions with a ternary material. It is possible to reduce costs while taking into account higher rate performance, cycle performance and energy density, thereby improving the comprehensive electrochemical performance of the positive electrode active material when used in batteries.

[0064] In some embodiments, the specific surface area of ​​lithium manganese iron phosphate is 11m 2 / g-21m 2 / g.

[0065] By setting the specific surface area of ​​lithium manganese iron phosphate within the above range, it is beneficial to improve the insertion and extraction reaction of lithium ions, thereby improving the energy density of the material and the battery's driving range, and it can also shorten the diffusion path of lithium ions inside the material, increase the diffusion rate of lithium ions, and thus improve the rate performance. When the specific surface area is within this range, it can also reduce agglomeration, improve dispersibility and stability, and thus extend the cycle life of the battery.

[0066] In some embodiments, the tap density of lithium manganese iron phosphate is 0.3 g / cm 3 -0.8g / cm 3 .

[0067] In some embodiments, the molecular formula of the ternary material is LiNi a Co b Mn c M d O2; wherein a+b+c+d=1, a≥0.5, b≤0.3, 0≤d≤0.05. M is selected from at least one of Zr, Sr, W, B, Nb, Al, Mg and Ti.

[0068] The high content of nickel (Ni) in ternary materials helps to increase the gram capacity and energy density and reduce the cost per watt-hour, so a ≥ 0.5 is set. The price of cobalt (Co) is relatively high, and by reasonably controlling the content of cobalt, it is possible to reduce costs while maintaining high performance.

[0069] The electrochemical performance of ternary materials can be further improved by doping with elements such as Zr, Sr, W, B, Nb, Al, Mg and Ti. Specifically, doping with zirconium (Zr) helps to improve the stability and mechanical strength of ternary materials, and effectively resist damage caused by volume expansion and contraction of materials; doping with strontium (Sr) can increase the volume of primary particles and unit cells of ternary materials, thereby increasing the compaction density of ternary materials, which is beneficial to improving the volume energy density of batteries; doping with tungsten (W) and boron (B) helps to optimize the crystal structure of ternary materials and improve the stability and performance of ternary materials; doping with niobium (Nb) can improve the cycle performance and thermal stability of nickel-rich ternary materials; doping with aluminum (Al) helps to improve the battery capacity and cycle stability of ternary materials. Aluminum has high electrochemical activity and can provide more lithium insertion sites, thereby increasing the energy storage capacity of the battery; doping with magnesium (Mg) and titanium (Ti) helps to improve the structural stability and thermal stability of ternary materials, which helps to improve the safety performance and cycle life of batteries.

[0070] By setting d≤0.05, the doping elements will not significantly change the main structure of the ternary material, maintaining the original stability and reliability of the ternary material. In addition, the amount of doping elements added is small, which can reduce costs while exerting the effect.

[0071] In some embodiments, the median particle size of the ternary material is 3 μm-10 μm. By setting the median particle size of the ternary material in the above range, the lithium ion diffusion path inside the ternary material particles is relatively short, which helps to improve the diffusion efficiency of lithium ions, thereby improving the charge and discharge performance of the battery. The particle sizes of the ternary material and lithium iron manganese phosphate are relatively close, which helps to disperse the stress in the positive active material more evenly and reduce the capacity decay caused by volume change.

[0072] In some embodiments, the lithium manganese iron phosphate includes a lithium manganese iron phosphate body and a carbon coating layer coating the lithium manganese iron phosphate body.

[0073] By setting a carbon coating layer, the electronic conductivity of the lithium iron manganese phosphate body can be improved, the internal resistance of the battery can be reduced, and the power density and energy density of the battery can be improved. The carbon coating layer also helps to form a conductive network on the surface of the lithium iron manganese phosphate body, thereby improving the efficiency of electron transmission and reducing the polarization phenomenon during the battery charging and discharging process. In addition, the carbon coating layer can also serve as a protective layer for the lithium iron manganese phosphate body, reducing the corrosion of substances such as hydrofluoric acid in the electrolyte, and the carbon coating layer can also enhance the structural stability of the lithium iron manganese phosphate body and improve the cycle performance.

[0074] In a second aspect, an embodiment of the present application provides a method for preparing a positive electrode active material, which is used to prepare the positive electrode active material as described above, comprising:

[0075] Provide ternary materials and lithium manganese iron phosphate;

[0076] The ternary material and lithium manganese iron phosphate are mixed in proportion to obtain a positive electrode active material.

[0077] In the embodiment of the present application, the ternary material and lithium manganese iron phosphate are mixed to form a positive electrode active material, and the preparation process is simple. The beneficial effects of the prepared positive electrode active material have been described above and will not be repeated here.

[0078] In some embodiments, before providing the ternary material and lithium iron manganese phosphate, the method further includes: preparing lithium iron manganese phosphate.

[0079] The preparation of lithium manganese iron phosphate includes:

[0080] Adding a phosphoric acid solution into a lithium source solution to react, thereby obtaining a hollow spherical lithium phosphate precursor;

[0081] Dispersing ferrous salt, manganese salt and lithium phosphate precursor in a solvent, and reacting to form lithium manganese iron phosphate precursor;

[0082] The lithium iron manganese phosphate precursor is sintered for the first time to obtain lithium iron manganese phosphate.

[0083] That is, the embodiment of the present application prepares hollow spherical lithium manganese iron phosphate by liquid phase method. Figure 1 As shown, phosphoric acid reacts with a lithium source to form a hollow spherical lithium phosphate precursor. Then, ferrous salt, manganese salt and lithium phosphate precursor are dispersed in a solvent, and iron ions and manganese ions are bonded to the hollow spherical lithium phosphate precursor by a solvothermal method. Since there are gaps between different monomers in the lithium phosphate precursor, it is convenient for iron ions and manganese ions to enter the interior of the hollow sphere, thereby forming a lithium iron manganese phosphate precursor. After the lithium iron manganese phosphate precursor is sintered, the sintering process can improve the crystallinity, enhance the bonding force between particles, and optimize the microstructure, thereby forming a stable lithium iron manganese phosphate.

[0084] Among them, it is preferred to disperse the ferrous salt, manganese salt and lithium phosphate precursor in ethylene glycol solvent. Since lithium phosphate is insoluble in ethylene glycol, it can maintain a hollow spherical structure during the reaction. And since lithium phosphate and lithium iron manganese phosphate have the same orthogonal system, hollow spherical lithium iron manganese phosphate is formed through structural conversion during the reaction.

[0085] The method for preparing lithium manganese iron phosphate provided in the embodiment of the present application can produce lithium manganese iron phosphate having a hollow spherical structure and a small particle size, and has excellent rate performance.

[0086] In some embodiments, a phosphoric acid solution is added to a lithium source solution to react to obtain a hollow spherical lithium phosphate precursor, including:

[0087] Add the phosphoric acid solution to the lithium hydroxide solution, stir at room temperature for 2-4 hours, and filter to obtain a first filtrate;

[0088] After the first filtered product is dried, a hollow spherical lithium phosphate precursor is obtained.

[0089] The phosphoric acid in the phosphoric acid solution reacts with the lithium hydroxide in the lithium hydroxide solution to form lithium phosphate, which self-assembles in the solution to form a hollow spherical lithium manganese iron phosphate. In the process of preparing the hollow spherical lithium phosphate, the reaction conditions are mild and the process is simple.

[0090] The molar ratio of phosphoric acid to lithium hydroxide can be set to 1:3 to form lithium phosphate (Li3PO4) and improve the utilization rate of phosphoric acid and lithium hydroxide.

[0091] In some embodiments, the molar ratio of the ferrous salt to the manganese salt is 1:9-9:1. The molar ratio of the ferrous salt to the manganese salt can be set as needed. It is understood that by setting the ratio of the two, different lithium manganese iron phosphates can be obtained, so that the ratio of the iron (Fe) element and the manganese (Mn) element in the lithium manganese iron phosphate changes.

[0092] That is, the molecular formula of the obtained lithium manganese iron phosphate is LiMn x Fe y PO4, 0<x<1, 0<y<1, 0<x+y≤1.

[0093] In some embodiments, the ratio of the sum of the amounts of the ferrous salt and the manganese salt to the amount of the lithium phosphate precursor is 1: 1. By setting the above ratio, the utilization rates of the ferrous salt, the manganese salt and the lithium phosphate precursor can be improved.

[0094] In some embodiments, the lithium manganese iron phosphate precursor is subjected to a first sintering, comprising:

[0095] In a protective atmosphere, the lithium manganese iron phosphate precursor is sintered at a temperature of 150°C-200°C for 5h-8h.

[0096] By sintering in a protective atmosphere, the oxidation reaction between the lithium phosphate precursor and oxygen during the sintering process can be avoided, thereby improving the sintering stability. By controlling the sintering temperature at 150°C-200°C, the lithium manganese iron phosphate precursor can undergo dehydration, recrystallization and other reactions. Sintering for 5h-8h can ensure sufficient reaction and form lithium manganese iron phosphate with a stable structure.

[0097] In some embodiments, after sintering the lithium manganese iron phosphate precursor, the method further comprises:

[0098] The sintered lithium manganese iron phosphate precursor is mixed with a carbon source and a first additive to obtain a coating material;

[0099] The coating material is sintered for a second time to obtain lithium manganese iron phosphate with a carbon coating layer.

[0100] By mixing the carbon source and the first additive with the sintered lithium iron manganese phosphate precursor and performing a second sintering, a carbon coating layer can be formed on the surface of the lithium iron manganese phosphate.

[0101] In some embodiments, the mass proportion of the carbon source in the coating material is 10%-20%. By controlling the mass proportion of the carbon source in the coating material to be within the above range, it is helpful to form a carbon coating layer of appropriate thickness.

[0102] In some embodiments, the carbon source comprises at least one of glucose, sucrose, and polyethylene glycol.

[0103] In some embodiments, the first additive includes at least one of Mg, Ti, Nb, Nd, Zr and Al, and the addition ratio of the first additive is 0 ppm-6000 ppm.

[0104] By adding a first additive comprising at least one of Mg, Ti, Nb, Nd, Zr and Al, the conductivity of the carbon coating layer can be improved, the ion diffusion performance can be optimized, the structural stability can be enhanced, and the energy density can be increased.

[0105] By setting the addition ratio of the first additive to 0ppm-6000ppm, the effect of the first additive can be brought into play, and problems such as blocking the lithium ion diffusion channel caused by excessive addition of the first additive can be reduced, thereby ensuring the material structure stability and electrochemical performance.

[0106] In some embodiments, the coating material is subjected to a second sintering, comprising:

[0107] The coating material is sintered at a temperature of 550°C-750°C for 5h-8h.

[0108] By performing a second sintering at 500℃-750℃, the carbon source can undergo a carbonization reaction to form a compact carbon coating layer that is tightly attached to the surface of lithium manganese iron phosphate, which can improve the conductivity and structural stability of the carbon coating layer. Setting the sintering time to 5h-8h helps the carbon coating layer to be tightly bonded to the lithium manganese iron phosphate and avoids the problem of performance degradation caused by sintering for too long.

[0109] In some embodiments, before providing the ternary material and lithium manganese iron phosphate, the method further includes:

[0110] Preparation of ternary materials.

[0111] The preparation of ternary materials includes:

[0112] Mixing a ternary material precursor, lithium carbonate and a second additive to obtain a first mixed material;

[0113] Under an oxygen-containing atmosphere, performing a third sintering on the first mixed material to obtain a first sintered material;

[0114] The first sintered material is crushed to obtain a ternary material.

[0115] Among them, the ratio of ternary material precursor, lithium carbonate and the second additive can be adjusted as needed. The ternary material precursor mainly includes three elements: nickel, cobalt and manganese, which are the core components of the ternary material. As a lithium source, lithium carbonate can react with the ternary material precursor during the sintering process to generate lithium nickel cobalt manganese oxide. By adding the second additive, the conductivity, structural stability and cycle performance of the ternary material can be improved.

[0116] In some embodiments, the second additive contains at least one of Zr, Sr, W, B, Nb, Al, Mg, and Ti.

[0117] In some embodiments, performing a third sintering on the first mixed material in an oxygen-containing atmosphere comprises:

[0118] In an atmosphere with an oxygen concentration of ≥95%, placing the first mixed material in a sintering furnace for sintering;

[0119] During the sintering process, the sintering furnace is first heated from room temperature to 450°C-600°C at a heating rate of 5°C / min, and kept warm for 3h-5h. Then, the sintering furnace is heated to 700°C-900°C at a heating rate of 5°C / min, and kept warm for 6h-10h.

[0120] In an oxygen-rich atmosphere (oxygen concentration ≥ 95%), it is helpful to form a stable oxidation environment, which helps the ternary material to form an ideal crystal structure and layered structure during the sintering process, thereby improving the electrochemical properties of the ternary material. During the sintering process, the sintering furnace is first heated from room temperature to 450℃-600℃ at a heating rate of 5℃ / min, and kept warm for 3h-5h. The heating rate is slow, which can make the material gradually adapt to the temperature change during the heating process. The decomposition of the ternary material precursor, the melting of lithium carbonate and partial reaction can occur at 450℃-600℃ for 3h-5h. Then heat up again and keep warm for 6h-10h in the temperature range of 700℃-900℃. Long-term heat preservation at high temperature helps the ion diffusion and reaction inside the material, and promotes the improvement and densification of the crystal structure. At the same time, high-temperature heat preservation can also improve the crystallinity and purity of the ternary material, thereby improving the electrochemical properties of the ternary material.

[0121] In a third aspect, an embodiment of the present application provides a positive electrode sheet, comprising a positive electrode foil and a positive electrode active layer coated on the positive electrode foil;

[0122] Wherein, the positive electrode active layer comprises the positive electrode active material as described above;

[0123] And / or, the positive electrode active material prepared by the method for preparing the positive electrode active material as described above.

[0124] The positive electrode sheet provided in the embodiment of the present application also has the beneficial effects of the above-mentioned positive electrode active material, which will not be described in detail here.

[0125] In some embodiments, the positive electrode sheet includes a positive electrode foil, a positive electrode active material, a positive electrode conductor, a positive electrode binder, and a dispersant.

[0126] The positive electrode foil may be a carbon-coated aluminum foil, the thickness of the aluminum foil in the carbon-coated aluminum foil may be 6 μm-20 μm, and the thickness of the carbon coating layer may be greater than 0 μm and less than or equal to 1.5 μm.

[0127] The carbon-coated aluminum foil includes an aluminum foil and a carbon coating layer coated on the aluminum foil. The carbon coating layer can optimize the surface properties of the aluminum foil, so that the positive electrode slurry can be more tightly and evenly attached to the aluminum foil, reducing the ineffective space, thereby improving the energy density of the battery. The thickness of the aluminum foil is set between 6μm-20μm, which not only ensures sufficient mechanical strength, but also reduces the weight of the battery and improves the energy density of the battery. The thickness of the carbon coating layer is set within the range of greater than 0μm and less than or equal to 1.5μm, which is ultra-thin and uniform, and helps to improve the overall performance of the battery.

[0128] Among them, the mass ratio of positive electrode active material, positive electrode conductor, positive electrode binder and positive electrode dispersant is (95-98): (0.5-2.5): (1-3): (0-1). Positive electrode active material is a key component for storage and release in the battery. By setting a higher proportion of positive electrode active material, it helps to improve the energy density of the battery. Under the same volume or mass, the battery can store more electrical energy, thereby extending the service time. An appropriate amount of positive electrode conductor helps to form an effective conductive network, reduce the internal resistance of the battery, and increase the electron and ion transmission rate, thereby enhancing the charge and discharge performance of the battery. The positive electrode binder plays a key role in maintaining the structural integrity and stability of the positive electrode sheet. By controlling the addition ratio of the positive electrode binder within a suitable range, it can ensure that the positive electrode active material does not fall off under the expansion and contraction during the charge and discharge process, maintain the stability of the structure, and thus improve the cycle life and safety of the battery. The dispersant helps to improve the fluidity of the positive electrode slurry and ensure that the positive electrode active material can be evenly distributed.

[0129] In some embodiments, the positive electrode conductive agent includes at least one of carbon nanotubes, graphene and acetylene black. Among them, carbon nanotubes have a high electrical conductivity, and using them as positive electrode conductive agents helps to reduce the internal resistance of the battery and improve the battery charging and discharging efficiency. And carbon nanotubes also have good mechanical strength and flexibility, can withstand the volume change of the positive electrode active material during the charging and discharging process of the battery, reduce the risk of particle fracture and structural damage of the positive electrode active material, thereby improving the cycle stability of the battery, and when carbon nanotubes are used as positive electrode conductive agents, the amount of addition can be reduced, which helps to increase the addition ratio of the positive electrode active material, thereby increasing the energy density of the battery. Graphene has a large specific surface area, which helps to form electrolyte storage gaps and increase the contact area between the positive electrode active material and the electrolyte, thereby enhancing the battery's charging and discharging efficiency. And graphene has excellent mechanical properties, which can improve the volume energy density of the positive electrode sheet, increase the bendability and peel strength of the positive electrode sheet, thereby improving the overall stability of the battery. In addition, graphene also has good thermal conductivity, which can reduce the thermal impedance of the battery and improve the thermal stability of the battery. Acetylene black has moderate thermal conductivity, low nitrogen cost, and good mechanical stability, which can inhibit material shedding and damage.

[0130] In some embodiments, the positive electrode binder includes at least one of polyvinylidene fluoride, polytetrafluoroethylene and polyacrylic acid. Polyvinylidene fluoride (PVDF) has excellent chemical stability and corrosion resistance, ensuring reliability and safety during use. PVDF also has good high voltage resistance, can remain stable under higher voltage conditions, and is not oxidized or deteriorated. It has good solubility and dissolution rate, can be evenly dispersed on the surface of the positive electrode slurry and the positive electrode sheet, thereby forming a uniform bonding layer, and it has high flexibility and bonding force, which can reduce the shedding phenomenon of the positive electrode active material during repeated expansion and contraction. Polytetrafluoroethylene (PTFE) has excellent corrosion resistance, strong stability, and good high temperature stability, and can be used for a long time at high temperature without decomposition. Polyacrylic acid (PAA) has good adhesion and can be connected to some functional groups on the surface of the positive electrode active material through hydrogen bonds, thereby forming a stable bonding layer, which helps to prevent the shedding and pulverization of the positive electrode active material. PAA can also effectively inhibit the volume expansion of the positive electrode active material during the charge and discharge process, thereby extending the cycle life of the battery. In addition, PAA itself has a small volume expansion coefficient and a large thermal diffusion coefficient. Using it as a positive electrode binder makes the battery safer when used under high-power charging and discharging and high temperature.

[0131] In a fourth aspect, an embodiment of the present application provides a battery, comprising the positive electrode sheet as above.

[0132] The battery provided in the embodiment of the present application also has the beneficial effects of the above-mentioned positive electrode active material, which will not be described in detail here.

[0133] In some embodiments, the battery further includes a negative electrode sheet, an electrolyte, and a separator.

[0134] Among them, the negative electrode sheet includes a negative electrode foil, a negative electrode active material, a negative electrode conductive agent and a negative electrode binder. The negative electrode foil is copper foil or copper mesh with a thickness of 4μm-12μm. Copper foil and copper mesh have excellent conductivity and low resistivity, and can quickly conduct current in the battery. Using them as negative electrode foil can provide an efficient conductive channel for the insertion and extraction process of lithium ions, thereby improving the battery's charge and discharge efficiency and response speed. Copper foil and copper mesh have high mechanical strength, which can protect the internal structure of the battery and increase the stability and strength of the internal structure of the battery. By controlling the thickness of the negative electrode foil to 4μm-12μm, it can not only ensure its structural strength, but also increase the energy density of the battery by reducing the mass of the negative electrode foil.

[0135] The negative electrode conductive agent is at least one of carbon nanotubes, carbon black and acetylene black. The advantages of carbon nanotubes and acetylene black have been described in the positive electrode conductive agent, and their application in the negative electrode conductive agent has similar advantages, which will not be repeated here. Carbon black has good electrical conductivity, can improve the conductivity of the negative electrode sheet, reduce the internal resistance of the battery, and carbon black can be evenly dispersed in the negative electrode active material to form a conductive network, accelerate the electron transfer rate, and improve battery performance. By using carbon black as a negative electrode conductive agent, the conductivity can be significantly improved on the basis of a lower addition amount, which helps to increase the addition amount of negative electrode active materials in the negative electrode sheet. Carbon black also has excellent chemical and physical stability, low cost, and good compatibility with other materials.

[0136] The electrolyte includes an electrolyte, an organic solvent and an additive. The electrolyte is at least one of lithium hexafluorophosphate (LIPF6), lithium bis(fluorosulfonyl)imide (LiFSI) and lithium bis(trifluoromethanesulfonyl)imide (LiTFSI). The organic solvent includes at least one of ethylene carbonate (EC), dimethyl carbonate (DMC), diethyl carbonate (DEC), polycarbonate (PC) and ethyl methyl carbonate (EMC). The additive includes at least one of vinylene carbonate (VC), vinyl sulfate (DTD), methylene disulfonate (MMDS), lithium bis(oxalatoborate) (LiBOB) and 1,3-propane sultone (PS), and the additive content accounts for 0.2%-1.5% of the total mass of the electrolyte.

[0137] The diaphragm includes a base film and a diaphragm coating coated on the base film. The base film side material is polypropylene (PP) or polyethylene (PE). The material of the diaphragm coating includes at least one of aluminum oxide, boehmite, magnesium hydroxide and barium sulfate. The thickness of the base film is 5μm-16μm, the thickness of the diaphragm coating is 0.5μm-5μm, and the tensile strength of the diaphragm is greater than 200MPa.

[0138] The vehicle provided in the embodiment of the present application also has the beneficial effects of the above-mentioned positive electrode active material, which will not be described in detail here.

[0139] The following examples are further described in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present application and are not intended to limit the scope of the present application. The experimental methods in the following examples that do not specify specific conditions are usually based on the conditions recommended by the manufacturer.

[0140] It should be noted that, except for the conditions stated in the embodiments and comparative examples, the conditions in the embodiments and comparative examples remain the same.

[0141] Example 1

[0142] In this embodiment: In the positive electrode sheet, the positive electrode active material includes 10% LiMn 0.6 Fe 0.4PO4 with 90% LiNi 0.8 Co 0.1 Mn 0.1 O2; in the negative electrode sheet, the negative electrode active material is graphite; the electrolyte in the electrolyte is LiPF6; the separator is a 12μm PP separator. The positive electrode sheet, the negative electrode sheet, the electrolyte and the separator are assembled to obtain a 2Ah lithium-ion battery.

[0143] Among them, LiMn 0.6 Fe 0.4 PO4 is a hollow spherical structure, LiMn 0.6 Fe 0.4 The median particle size of PO4 is 1.5 μm and the specific surface area is 15 m 2 / g, tap density is 0.7g / cm 3 ,LiNi 0.8 Co 0.1 Mn 0.1 The median particle size of O2 is 8 μm.

[0144] Example 2

[0145] In this embodiment: In the positive electrode sheet, the positive electrode active material includes 20% LiMn 0.6 Fe 0.4 PO4 with 80% LiNi 0.8 Co 0.1 Mn 0.1 O2; in the negative electrode sheet, the negative electrode active material is graphite; the electrolyte in the electrolyte is LiPF6; the separator is a 12μm PP separator. The positive electrode sheet, the negative electrode sheet, the electrolyte and the separator are assembled to obtain a 2Ah lithium-ion battery.

[0146] Among them, LiMn 0.6 Fe 0.4 PO4 is a hollow spherical structure, LiMn 0.6 Fe 0.4 The median particle size of PO4 is 1.5 μm and the specific surface area is 15 m 2 / g, tap density is 0.7g / cm 3 ,LiNi 0.8 Co 0.1 Mn 0.1 The median particle size of O2 is 8 μm.

[0147] Example 3

[0148] In this embodiment: In the positive electrode sheet, the positive electrode active material includes 30% LiMn 0.6 Fe 0.4 PO4 with 70% LiNi 0.8 Co 0.1 Mn 0.1O2; in the negative electrode sheet, the negative electrode active material is graphite; the electrolyte in the electrolyte is LiPF6; the separator is a 12μm PP separator. The positive electrode sheet, the negative electrode sheet, the electrolyte and the separator are assembled to obtain a 2Ah lithium-ion battery.

[0149] Among them, LiMn 0.6 Fe 0.4 PO4 is a hollow spherical structure, LiMn 0.6 Fe 0.4 The median particle size of PO4 is 1.5 μm and the specific surface area is 15 m 2 / g, tap density is 0.7g / cm 3 ,LiNi 0.8 Co 0.1 Mn 0.1 The median particle size of O2 is 8 μm.

[0150] Example 4

[0151] In this embodiment: In the positive electrode sheet, the positive electrode active material includes 40% LiMn 0.6 Fe 0.4 PO4 with 60% LiNi 0.8 Co 0.1 Mn 0.1 O2; in the negative electrode sheet, the negative electrode active material is graphite; the electrolyte in the electrolyte is LiPF6; the separator is a 12μm PP separator. The positive electrode sheet, the negative electrode sheet, the electrolyte and the separator are assembled to obtain a 2Ah lithium-ion battery.

[0152] Among them, LiMn 0.6 Fe 0.4 PO4 is a hollow spherical structure, LiMn 0.6 Fe 0.4 The median particle size of PO4 is 1.5 μm and the specific surface area is 15 m 2 / g, tap density is 0.7g / cm 3 ,LiNi 0.8 Co 0.1 Mn 0.1 The median particle size of O2 is 8 μm.

[0153] Example 5

[0154] In this embodiment: In the positive electrode sheet, the positive electrode active material includes 5% LiMn 0.5 Fe 0.5 PO4 with 95% LiNi 0.8 Co 0.1 Mn 0.1O2; in the negative electrode sheet, the negative electrode active material is graphite; the electrolyte in the electrolyte is LiPF6; the separator is a 12μm PP separator. The positive electrode sheet, the negative electrode sheet, the electrolyte and the separator are assembled to obtain a 2Ah lithium-ion battery.

[0155] Among them, LiMn 0.5 Fe 0.5 PO4 is a hollow spherical structure, LiMn 0.5 Fe 0.5 The median particle size of PO4 is 0.8 μm and the specific surface area is 18 m 2 / g, tap density is 0.6g / cm 3 ,LiNi 0.5 Co 0.2 Mn 0.3 The median particle size of O2 is 6 μm.

[0156] Example 6

[0157] In this embodiment: In the positive electrode sheet, the positive electrode active material includes 45% LiMn 0.5 Fe 0.5 PO4 with 55% LiNi 0.8 Co 0.1 Mn 0.1 O2; in the negative electrode sheet, the negative electrode active material is graphite; the electrolyte in the electrolyte is LiPF6; the separator is a 12μm PP separator. The positive electrode sheet, the negative electrode sheet, the electrolyte and the separator are assembled to obtain a 2Ah lithium-ion battery.

[0158] Among them, LiMn 0.5 Fe 0.5 PO4 is a hollow spherical structure, LiMn 0.5 Fe 0.5 The median particle size of PO4 is 0.8 μm and the specific surface area is 18 m 2 / g, tap density is 0.6g / cm 3 ,LiNi 0.5 Co 0.2 Mn 0.3 The median particle size of O2 is 6 μm.

[0159] Comparative Example 1

[0160] In this embodiment: In the positive electrode sheet, the positive electrode active material is 100% LiNi 0.8 Co 0.1 Mn 0.1 O2; in the negative electrode sheet, the negative electrode active material is graphite; the electrolyte in the electrolyte is LiPF6; the separator is a 12μm PP separator. The positive electrode sheet, the negative electrode sheet, the electrolyte and the separator are assembled to obtain a 2Ah lithium-ion battery.

[0161] Among them, LiNi 0.8 Co 0.1 Mn 0.1 The median particle size of O2 is 8 μm.

[0162] Comparative Example 2

[0163] In this embodiment: In the positive electrode sheet, the positive electrode active material is 100% LiMn 0.6 Fe 0.4 PO4; in the negative electrode sheet, the negative electrode active material is graphite; the electrolyte in the electrolyte is LiPF6; the separator is a 12μm PP separator. The positive electrode sheet, the negative electrode sheet, the electrolyte and the separator are assembled to obtain a 2Ah lithium-ion battery.

[0164] Among them, LiMn 0.6 Fe 0.4 PO4 is a hollow spherical structure, LiMn 0.6 Fe 0.4 The median particle size of PO4 is 1.5 μm and the specific surface area is 15 m 2 / g, tap density is 0.7g / cm 3 .

[0165] Comparative Example 3

[0166] In this embodiment: In the positive electrode sheet, the positive electrode active material includes 50% LiMn 0.6 Fe 0.4 PO4 with 50% LiNi 0.8 Co 0.1 Mn 0.1 O2; in the negative electrode sheet, the negative electrode active material is graphite; the electrolyte in the electrolyte is LiPF6; the separator is a 12μm PP separator. The positive electrode sheet, the negative electrode sheet, the electrolyte and the separator are assembled to obtain a 2Ah lithium-ion battery.

[0167] Among them, LiMn 0.6 Fe 0.4 PO4 is a hollow spherical structure, LiMn 0.6 Fe 0.4 The median particle size of PO4 is 1.5 μm and the specific surface area is 15 m 2 / g, tap density is 0.7g / cm 3 ,LiNi 0.8 Co 0.1 Mn 0.1 The median particle size of O2 is 8 μm.

[0168] Comparative Example 4

[0169] In this embodiment: In the positive electrode sheet, the positive electrode active material includes 70% LiMn 0.6 Fe 0.4PO4 with 30% LiNi 0.8 Co 0.1 Mn 0.1 O2; in the negative electrode sheet, the negative electrode active material is graphite; the electrolyte in the electrolyte is LiPF6; the separator is a 12μm PP separator. The positive electrode sheet, the negative electrode sheet, the electrolyte and the separator are assembled to obtain a 2Ah lithium-ion battery.

[0170] Among them, LiMn 0.6 Fe 0.4 PO4 is a hollow spherical structure, LiMn 0.6 Fe 0.4 The median particle size of PO4 is 1.5 μm and the specific surface area is 15 m 2 / g, tap density is 0.7g / cm 3 ,LiNi 0.8 Co 0.1 Mn 0.1 The median particle size of O2 is 8 μm.

[0171] The batteries assembled in Examples 1-6 and Comparative Examples 1-4 were tested for 0.1C gram capacity, 3C capacity retention rate and energy density. The results are shown in Table 1:

[0172] Table 1 Comparison of battery performance test results in different embodiments and comparative examples

[0173]

[0174] As can be seen from Table 1, in Comparative Example 1, the positive electrode active material uses 100% of the ternary material, and the 3C capacity retention rate is 57.82% (as shown in Table 1). Figure 2 As shown), in Comparative Example 2, the positive electrode active material uses 100% lithium manganese iron phosphate, and the 3C capacity retention rate is 92.96% (as shown Figure 3 The rate performance of the battery in Comparative Example 2 is better than that in Comparative Example 1, mainly because lithium manganese phosphate has a hollow spherical structure and a small particle size, which shortens the lithium extraction and insertion path during the charge and discharge process of the battery, which is conducive to improving the rate performance.

[0175] Comparing Examples 1-6 with Comparative Examples 1-4, mixing a certain proportion of lithium manganese iron phosphate into the positive electrode active material can improve its rate performance on the basis of using only ternary materials, and as the mixing proportion of lithium manganese iron phosphate increases, the rate performance of the battery gradually increases. When the mixing proportion of lithium manganese iron phosphate is 10%, the 3C capacity retention rate of the battery is 62.30% (Example 1, as Figure 4As shown), it is 4.5% higher than that of the battery using 100% ternary materials; when the blending ratio of lithium iron manganese phosphate is 20%, the 3C capacity retention rate of the battery is 68.45% (Example 2), which is 10.6% higher than that of the battery using 100% ternary materials; when the blending ratio of lithium iron manganese phosphate is 30%, the 3C capacity retention rate of the battery is 72.18% (Example 3), which is 14.4% higher than that of the battery using 100% ternary materials; when the blending ratio of lithium iron manganese phosphate is 40%, the 3C capacity retention rate of the battery is 76.50% (Example 4), which is 18.7% higher than that of the battery using 100% ternary materials; when the blending ratio of lithium iron manganese phosphate is 5%, the 3C capacity retention rate of the battery is 63.52% (Example 5), which is 100% higher than that of the battery using 100% ternary materials. When the blending amount of lithium iron manganese phosphate is 45%, the 3C capacity retention rate of the battery is 79.68% (Example 5), which is 21.9% higher than the battery using 100% ternary materials; when the positive electrode active material uses 100% lithium iron manganese phosphate, the 3C capacity retention rate of the battery is 92.96% (Comparative Example 2), which is 35.1% higher than the battery using 100% ternary materials; when the blending amount of lithium iron manganese phosphate is 50%, the 3C capacity retention rate of the battery is 80.82% (Comparative Example 3), which is 23.0% higher than the battery using 100% ternary materials; when the blending amount of lithium iron manganese phosphate is 70%, the 3C capacity retention rate of the battery is 89.10% (Comparative Example 4), which is 31.3% higher than the battery using 100% ternary materials.

[0176] However, when 100% lithium manganese iron phosphate is used, the actual gram capacity is 145 mAh / g (Comparative Example 2), which is 52 mAh / g lower than the actual gram capacity of 197 mAh / g (Comparative Example 1) when 100% ternary materials are used. When the proportion of lithium manganese iron phosphate increases, the actual gram capacity of the battery will decrease. When the blending amount of lithium iron manganese phosphate is 10%, the 0.1C gram capacity of the battery is 192mAh / g (Example 1), which is 5mAh / g lower than the gram capacity of the battery using 100% ternary materials; when the blending amount of lithium iron manganese phosphate is 20%, the 0.1C gram capacity of the battery is 186mAh / g (Example 2), which is 11mAh / g lower than the gram capacity of the battery using 100% ternary materials; when the blending amount of lithium iron manganese phosphate is 30%, the 0.1C gram capacity of the battery is 180mAh / g (Example 3), which is 17mAh / g lower than the gram capacity of the battery using 100% ternary materials; when the blending amount of lithium iron manganese phosphate is 40%, the 0.1C gram capacity of the battery is 171mAh / g (Example 4), which is 26mAh / g lower than the gram capacity of the battery using 100% ternary materials; When the blending amount of lithium iron manganese phosphate is 5%, the 0.1C gram capacity of the battery is 191mAh / g (Example 5), which is 6mAh / g lower than the gram capacity of the battery using 100% ternary materials; when the blending amount of lithium iron manganese phosphate is 45%, the 0.1C gram capacity of the battery is 169mAh / g (Example 6), which is 28mAh / g lower than the gram capacity of the battery using 100% ternary materials; when the blending ratio of lithium iron manganese phosphate is 50%, the 0.1C gram capacity of the battery is 167mAh / g (Comparative Example 3), which is 30mAh / g lower than the gram capacity of the battery using 100% ternary materials; when the blending ratio of lithium iron manganese phosphate is 70%, the 0.1C gram capacity of the battery is 158mAh / g (Comparative Example 4), which is 39mAh / g lower than the gram capacity of the battery using 100% ternary materials.

[0177] In addition, mixing a certain proportion of lithium iron manganese phosphate into the positive electrode active material can improve the energy density of the battery based on the use of lithium iron manganese phosphate alone, and as the mixing proportion of the ternary material increases, the energy density gradually increases. When the blending ratio of lithium iron manganese phosphate is 10% and the blending ratio of the ternary material is 90%, the energy density of the battery is 262Wh / kg (Example 1), which is 62Wh / kg higher than that of the battery using only lithium iron manganese phosphate; when the blending ratio of lithium iron manganese phosphate is 20% and the blending ratio of the ternary material is 80%, the energy density of the battery is 256Wh / kg (Example 2), which is 56Wh / kg higher than that of the battery using only lithium iron manganese phosphate; when the blending ratio of lithium iron manganese phosphate is 30% and the blending ratio of the ternary material is 70%, the energy density of the battery is 250Wh / kg (Example 3), which is 50Wh / kg higher than that of the battery using only lithium iron manganese phosphate; when the blending ratio of lithium iron manganese phosphate is 40% and the blending ratio of the ternary material is 60%, the energy density of the battery is 243Wh / kg (Example 4), which is 43Wh / kg higher than that of the battery using only lithium iron manganese phosphate ; When the blending ratio of lithium iron manganese phosphate is 5% and the blending ratio of the ternary material is 95%, the energy density of the battery is 259Wh / kg (Example 5), which is 59Wh / kg higher than that of the battery using only lithium iron manganese phosphate; when the blending ratio of lithium iron manganese phosphate is 45% and the blending ratio of the ternary material is 55%, the energy density of the battery is 241Wh / kg (Example 6), which is 41Wh / kg higher than that of the battery using only lithium iron manganese phosphate; when the blending ratio of lithium iron manganese phosphate is 50% and the blending ratio of the ternary material is 50%, the energy density of the battery is 237Wh / kg (Comparative Example 3), which is 37Wh / kg higher than that of the battery using only lithium iron manganese phosphate; when the blending ratio of lithium iron manganese phosphate is 70% and the blending ratio of the ternary material is 30%, the energy density of the battery is 233Wh / kg (Comparative Example 4), which is 33Wh / kg higher than that of the battery using only lithium iron manganese phosphate.

[0178] In addition, lithium manganese iron phosphate has an olivine structure and has excellent cycle performance. In Example 1, by mixing 10% lithium manganese iron phosphate into the positive electrode active material, the number of cycles can reach more than 2000 (such as Figure 5 shown).

[0179] In summary, the present application, by having the positive electrode active material simultaneously include a ternary material and hollow spherical lithium manganese iron phosphate, can save costs by blending hollow spherical lithium manganese iron phosphate into the ternary material, and controlling the blending ratio of lithium manganese iron phosphate in the positive electrode active material within the range of greater than 0% and less than 50%, while taking into account rate performance, cycle performance and energy density, thereby ensuring comprehensive electrochemical performance.

[0180] The embodiments of the present application are introduced in detail above. Specific examples are used in this article to illustrate the principles and implementation methods of the present application. The description of the above embodiments is only used to help understand the method and core idea of ​​the present application. At the same time, for technical personnel in this field, according to the idea of ​​the present application, there will be changes in the specific implementation method and application scope. In summary, the content of this specification should not be understood as a limitation on the present application.

Claims

1. A positive electrode active material, characterized in that: Including ternary materials and lithium manganese iron phosphate; Wherein, the mass of the lithium manganese iron phosphate is A, the total mass of the ternary material and the lithium manganese iron phosphate is B, and the following is satisfied: 0<A / B<50%; The lithium manganese iron phosphate has a hollow spherical structure, and the median particle size of the lithium manganese iron phosphate is 0.5 μm-3 μm.

2. The positive electrode active material according to claim 1, characterized in that The specific surface area of ​​the lithium manganese iron phosphate is 11m 2 / g-21m 2 / g; And / or, the tap density of the lithium manganese iron phosphate is 0.3 g / cm 3 -0.8g / cm 3 .

3. The positive electrode active material according to claim 1, characterized in that The molecular formula of the ternary material is LiNi a Co b Mn c M d O2; where a+b+c+d=1, a≥0.5, b≤0.3, 0≤d≤0.05; M is selected from at least one of Zr, Sr, W, B, Nb, Al, Mg and Ti.

4. The positive electrode active material according to claim 1, characterized in that The median particle size of the ternary material is 3 μm-10 μm.

5. The positive electrode active material according to any one of claims 1 to 4, characterized in that: The lithium iron manganese phosphate comprises a lithium iron manganese phosphate body and a carbon coating layer coating the lithium iron manganese phosphate body.

6. A method for preparing a positive electrode active material, for preparing the positive electrode active material according to any one of claims 1 to 5, characterized in that: include: Provide ternary materials and lithium manganese iron phosphate; The ternary material and the lithium manganese iron phosphate are mixed according to a certain proportion to obtain a positive electrode active material.

7. The method for preparing a positive electrode active material according to claim 6, characterized in that: Before providing the ternary material and lithium manganese iron phosphate, the method further includes: preparing the lithium manganese iron phosphate; The preparation of the lithium manganese iron phosphate comprises: Adding a phosphoric acid solution into a lithium source solution to react, thereby obtaining a hollow spherical lithium phosphate precursor; Dispersing ferrous salt, manganese salt and lithium phosphate precursor in a solvent, and reacting to form lithium manganese iron phosphate precursor; The lithium iron manganese phosphate precursor is sintered for the first time to obtain lithium iron manganese phosphate.

8. The method for preparing a positive electrode active material according to claim 7, characterized in that: The phosphoric acid solution is added to the lithium source solution to react to obtain a hollow spherical lithium phosphate precursor, comprising: Add the phosphoric acid solution to the lithium hydroxide solution, stir at room temperature for 2-4 hours, and filter to obtain a first filtrate; After the first filtered product is dried, the hollow spherical lithium phosphate precursor is obtained.

9. The method for preparing a positive electrode active material according to claim 7, characterized in that: The molar ratio of the ferrous salt to the manganese salt is 1:9-9:1; And / or, the ratio of the sum of the amounts of the ferrous salt and the manganese salt to the amount of the lithium phosphate precursor is 1:

1.

10. The method for preparing a positive electrode active material according to claim 7, characterized in that: The first sintering of the lithium iron manganese phosphate precursor comprises: In a protective atmosphere, at a temperature of 150° C. to 200° C., the lithium manganese iron phosphate precursor is sintered for 5 h to 8 h.

11. The method for preparing a positive electrode active material according to claim 7, characterized in that: After sintering the lithium manganese iron phosphate precursor, the method further comprises: The sintered lithium manganese iron phosphate precursor is mixed with a carbon source and a first additive to obtain a coating material; The coating material is sintered for a second time to obtain the lithium manganese iron phosphate with a carbon coating layer.

12. The method for preparing a positive electrode active material according to claim 11, characterized in that: In the coating material, the mass proportion of the carbon source is 10%-20%; And / or, in the coating material, the first additive comprises at least one of Mg, Ti, Nb, Nd, Zr and Al, and the addition ratio of the first additive is 0 ppm-6000 ppm.

13. The method for preparing a positive electrode active material according to claim 11, characterized in that: The second sintering of the coating material comprises: The coating material is sintered at a temperature of 550° C.-750° C. for 5 h-8 h.

14. The method for preparing a positive electrode active material according to any one of claims 6 to 13, characterized in that: Before providing the ternary material and lithium manganese iron phosphate, the method further includes: preparing the ternary material; The preparation of the ternary material comprises: Mixing a ternary material precursor, lithium carbonate and a second additive to obtain a first mixed material; Under an oxygen-containing atmosphere, performing a third sintering on the first mixed material to obtain a first sintered material; The first sintered material is crushed to obtain the ternary material.

15. The method for preparing a positive electrode active material according to claim 14, characterized in that: The step of performing a third sintering on the first mixed material in an oxygen-containing atmosphere comprises: In an atmosphere with an oxygen concentration of ≥95%, placing the first mixed material in a sintering furnace for sintering; During the sintering process, the sintering furnace is first heated from room temperature to 450°C-600°C at a heating rate of 5°C / min, and kept warm for 3h-5h, and then heated to 700°C-900°C at a heating rate of 5°C / min, and kept warm for 6h-10h.

16. A positive electrode sheet, characterized in that: It comprises a positive electrode foil and a positive electrode active layer coated on the positive electrode foil; Wherein, the positive electrode active layer comprises the positive electrode active material according to any one of claims 1 to 5; And / or, a positive electrode active material prepared by the method for preparing a positive electrode active material according to any one of claims 6 to 15.

17. A battery, characterized in that: Comprising the positive electrode sheet as claimed in claim 16.

Citation Information

Patent Citations

  • Monatomic doped lithium manganese iron phosphate composite material and preparation method and application thereof

    CN116169262A

  • Positive electrode active material and positive electrode plate of lithium ion battery, and preparation method and application of positive electrode active material and positive electrode plate

    CN116864677A

  • High-nickel single-crystal nickel-cobalt-manganese ternary positive electrode material as well as preparation method and application thereof

    CN117071072A

Cited By

  • Positive plate, lithium ion battery and electric device

    CN120261546A

  • Positive electrode, lithium-ion battery and power-consuming device

    CN120261546B

  • Lithium manganese iron phosphate composite material coated with lithium titanium aluminum phosphate, preparation method of lithium manganese iron phosphate composite material and lithium ion battery

    CN121726376A

  • Positive electrode active material and preparation method therefor, positive electrode sheet, and battery

    EP4783259A1

  • Positive electrode active material and preparation method therefor, positive electrode sheet, and battery

    WO2026123631A1